Managing and Funding Early Childhood Education in Nigeria: The Way Forward - Igba Ji, Clement; Abdullahi, Bashir; Alhaji, Nura (Kashere Journal of Education, 2025)
This paper discusses the current management, funding, strategies, and financing procedures of Early Childhood Education (ECE) in Nigeria, with the sole goal of suggesting practical strategies for its effective investment and management. The paper acknowledges the commitment and effort of the Nigerian Governments and the assistance of the groups, people and overseas sponsors in funding ECE programs. The paper emphasises that there may be nonetheless a long way to head towards imparting good enough management and finances for preschool education and instructors/carers. The delivery of appropriate facilities and stimulating the gaining of knowledge of substances in addition to supervision of ECCD programs. Towards this, expanded government allocations, sustained worldwide assistance, economic allocation to ECE teacher training institutions, equity funding and price-sharing strategies were encouraged